Analysis of Cognitive Diagnostic Assessment (CDA) in Differentiated Learning on English Subject Phase D - Rini Ekayati; M. Meisuri (Randwick International of Education and Linguistics Science Journal, 2023)
This article presents a meticulous examination of Cognitive Diagnostic Assessment (CDA) in the context of Phase D differentiated learning, with a specific emphasis on English subjects. The study investigates the practice of diagnostic assessment in differentiated learning in Phase D English diagnostic courses and evaluate the challenges teachers face in implementing cognitive diagnostic assessment in differentiated learning. Through a qualitative inquiry, the research administrated questioner and an interview by involving 3 (three) English teacher at the seventh-grade students as the techniques of collecting data, and further analyzed the data by conducting data coding, interpretation, and triangulation. The study concluded that the practice of CDA was based on their prior knowledge of the assessment, and their believe that cognitive diagnostic assessment needs to be conducted in the differentiated learning on English subject phase D. Further, the assessment is distributed by using rubrics and checklist diagnostic tools, and rely on observation method. The respondent believed that CDA strongly informs their differentiated instructional practice and see moderate impact on their instructional practice in conducting it, and they need support from the institution to strengthen their capability in conducting CDA. Related to the challenging of CDA, the most challenges aspects are in struggling with time limitations in implementing CDA, dealing with student reluctance or opposition, interpreting assessment outcomes, and training on cognitive diagnostic tools.